Your physique : a magazine for men who want to improve their bodies. (Montréal : Your Physique Publishing.)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 16 Hopkins Avenue, Jersey City, NJ
Engels
Periodiek